Crustacea biodiversity in tubes of Ceriantharia (Cnidaria; Anthozoa), including the description of a novel species of Amphipoda from southeastern Brazil - Ceriello, Hellen [UNESP]; Senna, André R.; Andrade, Luiz F.; Stampar, Sérgio N. [UNESP] (Taylor & Francis, 2021)
This study investigates ceriantharian tubes to better understand the biodiversity of marine benthic crustaceans. The inner and outer surfaces of eight tubes of Ceriantharia from the northern coast of the state of São Paulo, Brazil, were analyzed. We observed 14 taxa of crustaceans, including one novel species, Podocerus carmelina sp. nov. We also report two new location records for previously known species and provide an identification key for Podocerus species with type localities in the Atlantic Ocean. The new species can be easily differentiated from its congeners by the following features: pereonite 3 with weak dorsal carina; gnathopod 2 carpus indistinct, almost entirely fused to propodus, propodus bearing several facial short plumose setae, palm defined by a proximal blunt projection, with a subtriangular tooth medially, a ‘u-shaped’ concavity and a crenulated lobe distally; pereonite 4 elongated, about 2.2 × deeper than wide; pereonites 5–6 anteroventral corner with a subacute projection; coxa 5 anteroventral corner with a notch, forming an acute spine; telson dorsal lobe with three stout setae, with naked lateral margins; uropod 2 outer ramus with one subapical long and stout plumose seta. Publication LSID: lsid:zoobank.org:act:B733959C-C1E7-464B-88FB-AF5D2C6347F8.
Keywords: Benthic marine invertebrates; Podocerus; taxonomy; tube-dwelling anemone